2009
DOI: 10.1007/s11187-009-9224-4
|View full text |Cite
|
Sign up to set email alerts
|

University spillovers and new business location in high-technology sectors: Spanish evidence

Abstract: University spillovers, Scientific knowledge, Technological knowledge, Business location, C29, L26, M13, O18, O33,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 47 publications
4
29
0
Order By: Relevance
“…Karnani (2013) has criticized an overemphasis on codified knowledge in the literature, which disregards tacit knowledge, particularly in the highly relevant sector of university spin-offs. In this domain, the creation of start-ups using knowledge provided by non-commercial institutions such as universities (Acosta et al, 2011; or research institutions (Cappelli et al, 2014) has been identified as an important source of knowledge spillover. As new employees, university graduates often transfer knowledge to spin-offs in the vicinity (Acosta et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Karnani (2013) has criticized an overemphasis on codified knowledge in the literature, which disregards tacit knowledge, particularly in the highly relevant sector of university spin-offs. In this domain, the creation of start-ups using knowledge provided by non-commercial institutions such as universities (Acosta et al, 2011; or research institutions (Cappelli et al, 2014) has been identified as an important source of knowledge spillover. As new employees, university graduates often transfer knowledge to spin-offs in the vicinity (Acosta et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge spillovers have been operationalized using e.g. codified knowledge -which can be easily transferred in written form (Acosta et al, 2011;) -or tacit knowledge sources, incorporated in human capital (Klepper, 2007). In particular, the case of innovative knowledge disregarded by incumbent companies and research institutions yet turned into entrepreneurial opportunities by newly established competitors has been emphasized Audretsch and Keilbach, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When there are greater levels of university-based knowledge spillovers, there are likely to be higher levels of new venture startups located around the university . The highly sophisticated, technological requirements of RM venturing indicate that new RM ventures are most likely to locate themselves around the university in order to capitalize on localized university knowledge spillovers (Acosta et al, 2011;. By being in close proximity to the university, RM ventures may benefit from smoother transmission of tacit knowledge (Kolympiris and Kalaitzandonakes, 2013).…”
Section: Knowledge Spillover and Creationmentioning
confidence: 99%
“…The flow of knowledge has important potential benefits for regions because of spillovers from university to industry affecting not only technology, but other relevant variables for the economic system (Jaffe, 1989;Jaffe et al, 1993;Anselin et al, 1997;Anselin et al, 2000;Verspagen and Schoenmakers, 2000;Maurseth and Verspagen, 2002;Acosta and Coronado, 2003;Agrawal and Cockburn, 2003;Fischer and Varga, 2003;Audretsch et al, 2005;Calderini and Scellato, 2005;Abramovsky et al, 2007;Acosta et al, 2011a). The proliferation of a consistent literature illustrating the importance of physical proximity for knowledge flows and for the promotion and development of innovation and new firm formation, along with the high degree of self-government enjoyed by many European regions, makes it clear that the study of university knowledge is relevant not only in national or supranational contexts, but also at the regional level.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%